Comparative Analysis of the Features of Conjugal Love based on Familiaris consortio and Amoris laetitia - Pomarańska, Renata (Studia Warmińskie, 2022)
The article discusses the characteristics of conjugal love based on two apostolic exhortations on marriage and family. One is Familiaris consortio by John Paul II and the other is Amoris laetitia by Pope Francis. The emphasis is on conjugal love, but the exhortations refer to the family inherent in marriage, hence this aspect also appears in the article. The text is divided into four parts. The first covers the biblical-theological origins of marital love in the papal exhortations, the second focuses on the characteristics of love between a man and a woman in Familiaris consortio, the third discusses the characteristics of true marital love in Amoris laetitia, while the fourth shows the similarities and differences in the presentation of the characteristics of this love in the two documents.